Trouble sources and students’ self-repair strategies in maintaining dynamics and understanding in online communication - Miftachudin; Rudi Hartono; Sri Wahyuni (Erudita: Journal of English Language Teaching, 2025)
The present study aims to explore trouble sources and students’ repair strategies in maintaining communication dynamics and understanding. Using a descriptive qualitative method within the framework of conversation analysis, the researcher tries to describe, explain, and interpret the data collection. The data were in the form of words, phrases, or sentences populated from genuine conversations in discussion sessions of online doctoral student class interaction at one of the state universities in Central Java. Six doctoral students in a class of language education science participated in this study. The data sources were derived from voice recordings of class interactions during discussion sessions. The data were populated through four stages of recording, viewing, transcribing, and analyzing (RVIA). The study findings demonstrate that the repair strategies involved pauses, fillers, hedges, replacement, code mixing, repetition, and expansion. Meanwhile, the trouble sources were identified as a lack of knowledge and language errors (syntax and lexical aspects). By understanding the concept of repair strategies, students had the opportunity to modify, organize, and maintain communication dynamics and understanding. Meanwhile, teachers could use the knowledge to manage the class and assist students to be more proficient in delivering their ideas efficiently and accurately.